THE ROLE OF INTERNATIONAL INVESTMENT ON ECONOMIC GROWTH OF CENTRAL ASIA - Azizbek Nabiev Inomjon ugli (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Central Asian nations are heavily tied to international capital, which remain a key driving force behind the region's growth and development. This study investigates the impact of foreign direct investments (FDI), portfolio investments, and international financial support on economic development in Central Asia. So with rich natural resources oil, gas, minerals, etc and strategic position the region is still an attraction for other world investors seeking for other investment opportunities. But in spite of these benefits, there are multiple challenges that restrain the environment for investment. Political instability, bureaucratic inefficiencies, corruption, and legal uncertainties create hurdles that investors cannot easily jump to enter the market with confidence. This paper discusses international investments in key sectors: energy, transportation infrastructure, manufacturing, and services. For Central Asian nations to improve the investment environment they must adopt strategic reforms. The recommendations are: To attract and retain foreign investment, the economy should be diversified and a transparent and investor-friendly regulatory system put in place with strengthened regional economic cooperation. It is, therefore, possible that these countries can ensure a stable and business friendly environment through which they can better attract and bond foreign capital for sustainable and long-term economic development in a highly competitive global market.